Analysis of Interpersonal Communication between Mother and Child to the Readiness of Menarche in MI Ma’arif Polorejo Babadan Ponorogo District - Afifa Ika Kridawati; Byba Melda Suhita; Nurwijayanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Menstruation can be a scary experience. Adequate preparation before menarche have a significant impact on girls' early experience of menarche. How does a mother communicating with her daughter about menarche and menstrual problems may affect future experience the girl. The purpose of this study was to analyze the influence of the mother's interpersonal communication factors on the child's readiness to come of menarche at MI Ma'arif Polorejo. This research design uses a qualitative method with a case study approach. The sampling technique used was snowball sampling. The informants used are the mothers of students who have not experienced menarche. The results of the study using in-depth interviews with 9 informants showed that interpersonal communication between mothers and children was still lacking, this was due to the lack of knowledge from mothers and the intensity of communication between mothers and children which could not be done intensively, so there are students who are prepared for menarche, and students are not prepared for menarche. Constraints expressed by the informant informant because knowledge is limited, and the child has not experienced menarche, so that the informants had not been able to provide detailed information.